“There Was a Sense That Our Load Had Been Lightened”: Evaluating Outcomes of Virtual Ethics Rounds for Veterinary Team Members - Quain, Anne; Mullan, Siobhan; Ward, Michael P. (Frontiers in Veterinary Science, 2022)
Clinical ethics support services (CESS) are employed in healthcare to improve patient care and help team members develop skills to recognize and navigate ethically challenging situations (ECS). The objective of this study was to evaluate the impact of ethics rounds, one form of CESS, on veterinary team members. An anonymous, online mixed-methods survey incorporating a 15-item instrument designed to assess the outcomes of moral case deliberation originally developed for human healthcare workers (the Euro-MCD 2.0), was developed. The survey was administered to veterinary team members prior to and following participation in a 90-minute virtual ethics rounds session. A total of 23 sessions of virtual ethics rounds were held. In total, 213 individuals participated, and 89 completed both surveys (response rate 41.8%). Most respondents were female (n=70, 81%). Most were veterinarians (n= 51, 59%), followed by other veterinary team members (practice manager, animal attendant) (n=18, 21%), veterinary nurses or animal health technicians (n=10, 12%) and veterinary students (n=8, 9%). Age ranged from 20 to 73 (median 41, IQR 32-52, n=87). While there was no statistically significant difference between overall modified Euro-MCD 2.0 scores between T1 and T2, there were statistically significant changes in 7 out of 15 Euro-MCD 2.0 items in the domains of moral competence and moral teamwork. Reflexive thematic analysis of free-text responses identified themes including the types, impact and barriers to resolving ECS, the impacts of ethics rounds on veterinary team members and constraints preventing veterinary team members from speaking up in the face of ECS. While participants largely described the impact of ethics rounds as beneficial (for example, by facilitating clarification of thinking about ECS, allowing participants to see ECS from the perspective of others and providing a safe space for discussion), reflecting on ECS could be stressful for participants. Active participation in ethics rounds may be inhibited in in the context of power imbalance, or in settings where bullying occurs. Overall, carefully facilitated ethics rounds has the potential to improve the ability of veterinary team members to identify and navigate ECS, and potentially mitigate moral distress.